Tharu community's perception on climate changes and their adaptive initiations to withstand its impacts in Western Terai of Nepal - Maharjan S. K.; Sigdel, E. R.; Sthapit, B.R.; Regmi B.R. (2011)
This paper brings out perceptions and observations of Tharu communities (Rana and Chaudhary), inhabitants of Shakarpur VDC of Kanchanpur and Gadariya VDCs of Kailali on climate change and its impacts on their livelihood strategies over the years. In addition, the paper explores some initiatives taken by the local communities to minimize its effects and impacts. Focus Group Discussions (FGD) were organized to collect and analyze vulnerability contexts on climate change and its impact on various sectors like, agriculture, forest, livestock, biodiversity, infrastructure, human casualties and water sources. Similarly, information on available service providers and their contribution was garnered through secondary sources. Local communities are facing these changes over the time and adapting strategies as per their own traditional knowledge, skills and information. Most of these strategies are biodiversity friendly, economically viable and socially acceptable. However, these innovative steps should be shared for larger scale dissemination after validating with scientific review and justifications.